A study on the skills of master of arts in research psychology graduates from the employers’ perspective - Fynn, A.W.R.; Dladla, S.N.; Erasmus, H. (South African Journal of Higher Education, 2019)
There is limited research into Research Psychology in general and even less research into employers’ expectations of graduates from Research Psychology programmes. Calls from higher education institutions to improve graduate employability demonstrate the importance of exploring employer expectations. The method employed in this study was a cross-sectional design. Employers were surveyed to determine the types of industry in which graduates are employed, the institutions that employ the graduates and the skills required for their employment. Descriptive statistics and frequency counts were carried out to report the results. The study found that employers place much emphasis on the importance of soft skills, which is in contrast to the weight given to hard skills. In terms of research‑specific skills, employers focus less on the academic research skills and more on the basic research skills that research programmes often take for granted. The matching of the organisation to the individual was considered important. Although this falls outside the offerings of research programmes, this match ensures the employment of the graduate and increases human capital development within organisations. The research problem was that while the existence of the skills gap between training outcomes and employer expectations is widely documented, relatively little research has been conducted into the expectations of employers of graduates within the field of Research Psychology. The study contributes to the understanding of the expectations of employers that affect employability outcomes and destinations of Research Psychology graduates.